Coarsely crystalline cryogenic cave carbonate: a new archive to estimate the last glacial minimum permafrost depth in Central Europe - Žák, Karel; Mangini, Augusto (Climate of the past, 2012)
Cryogenic cave carbonate (CCC) represents a specific type of speleothem whose precipitation is triggered by freezing of mineralized karst water. Coarsely crystalline CCC, which formed during slow freezing of water in cave pools, has been reported from 20 Central European caves located in Germany, the Czech Republic, Slovakia and Poland. All these caves are situated in an area which was glacier-free during the Weichselian. Whereas the formation of usual types of speleothems in caves of this region usually ceased during the glacials, coarsely crystalline CCC precipitation was restricted to glacial periods. Since this carbonate type represents a novel, useful paleoclimate proxy, data from its Weichselian occurrences in caves in Central Europe were collected, including their C and O stable isotope values, U-series ages and depth below the surface. When using only the CCC data from caves with limited cave ventilation, the permafrost depths of the Weichselian can be estimated to be at least 65 m in the lowlands and uplands. An isolated CCC find indicates that Weichselian permafrost penetrated to a depth of at least 285 m in the High Tatra mountains, Slovakia. A model of the formation of coarsely crystalline CCC assumes its formation especially during periods of permafrost thawing. U-series data confirm that permafrost depth changed and CCC precipitation in deep caves occurred repeatedly in the studied area during marine isotope stages 4, 3 and 2. One important phase of coarsely crystalline CCC formation related to permafrost thawing occurred between 40 and 21 ka BP, and the last phase of its formation was related to the final permafrost destruction between 17 and 12 ka BP.